Analysis on Emergency Treatment Effect of Tritium Leakage Accident in the Nuclear Reactor Under Different Ventilation Conditions - Li, Changjun; Cai, Xingfu; Xiao, Mingqing; Huo, Yonggang; Xu, Peng; Li, Sufen (Frontiers in Energy Research, 2022)
The high-pressure tritium leakage is a typical nuclear leakage accident, which can cause radioactive harm. The study aims at the tritium leakage problem in the high-pressure vessel of a nuclear reactor, installing a typical tritium leakage scenario and establishing the thermodynamic model of tritium leakage behavior which describes the transient process of tritium leakage. To analyze the effect of different ventilation scenes on tritium removal efficiency, the study sets up six different ventilation scenes and carries out the numerical simulation of tritium migration and mixing behavior based on Fluent. The result shows that different ventilation scenes will form different swirl distributions; the more complex the swirl distribution is, the faster the tritium concentration decreases. The shortest time required to decrease tritium concentration in space to the background level at the ventilation rate of 1 m3 s−1 is about 830 s and the longest time is about 1100 s. The overall tritium removal efficiency can be effectively improved when the swirl concentration distribution area is opposite to the exhaust outlet position. The setting method of ventilation is optimized, which provides technical support for the emergency treatment of tritium leakage accidents in the room.